Oxoisoaporphine alkaloid derivative 8-1 reduces Aβ1-42 secretion and toxicity in human cell and Caenorhabditis elegans models of Alzheimer's disease. (September 2017) - Huang, Liyingzi; Luo, Yunfeng; Pu, Zhijun; Kong, Xianghui; Fu, Xiang; Xing, Huanhuan; Wei, Shenqi; Chen, Wei; Tang, Huang
Abstract: Alzheimer's disease (AD) is a multifactorial neurodegenerative disease and a growing health problem worldwide. Because the drugs currently used to treat AD have certain drawbacks such as single targeting, there is a need to develop novel multi-target compounds, among which oxoisoaporphine alkaloid derivatives are promising candidates. In this study, the possible anti-AD activities of 14 novel oxoisoaporphine alkaloid derivatives that we synthesized were screened and evaluated. We found that, in the 14 novel derivatives, compound 8-1 significantly reduced Aβ1-42 secretion in SH-SY5Y cells overexpressing the Swedish mutant form of human β-amyloid precursor protein (APPsw). Next, we found that compound 8-1 could down-regulate the expression level of β-amyloid precursor protein (APP) in APPsw cells. Moreover, compound 8-1 significantly delayed paralysis in the Aβ1-42 -transgenic Caenorhabditis elegans strain GMC101, which could be explained by the fact that compound 8-1 down-regulated acetylcholinesterase activity, protected against H2 O2 -induced acute oxidative stress and paraquat-induced chronic oxidative stress, and enhanced autophagy activity. Taken together, our data suggest that compound 8-1 could attenuate the onset and development of AD. Highlights: Compound 8-1 reduced secreted Aβ1-42 level in APPsw cells which were SH-SY5Y cells overexpressing human β-amyloid precursor protein (APP). Compound 8-1 delayed the paralysis in Aβ1-42 -transgenic C . elegans GMC101. Compound 8-1 could significantly protect Aβworms GMC101 against H2 O2 -induced acute oxidative stress and paraquat-induced chronic oxidative stress. Compound 8-1 reduced AChE activity in Aβ1-42 -transgenic C. elegans GMC101. Compound 8-1 enhanced autophagy initiation gene bec-1 expression in GMC101 and could reduce autophagy substrate protein SQST-1 in BC12921.